Cation/Anion Dual‐Vacancy Pair Modulated Atomically‐Thin Sex‐Co3S4 Nanosheets with Extremely High Water Oxidation Performance in Ultralow‐Concentration Alkaline Solutions. Issue 15 (1st March 2022) - Gu, Xiangyao; Li, Shuangshuang; Shao, Wenqian; Mu, Xueqin; Yang, Yuxin; Ge, Yu; Meng, Weitao; Liu, Guangxiang; Liu, Suli; Mu, Shichun
Abstract: The density functional theory calculation results reveal that the adjacent defect concentration and electronic spin state can effectively activate the Co III sites in the atomically thin nanosheets, facilitating the thermodynamic transformation of *O to *OOH, thus offering ultrahigh charge transfer properties and efficiently stabilizing the phase. This undoubtedly evidences that, for metal sulfides, the atom‐scale cation/anion vacancy pair and surface electronic spin state can play a great role in enhancing the oxygen evolution reaction. Inspired by the theoretical prediction, interconnected selenium (Se) wired ultrathin Co3 S4 (Se x ‐Co3 S4 ) nanosheets with Co/S (Se) dual‐vacancies (Se1.0 ‐Co3 S4 ‐VS/Se ‐VCo ) pairs are constructed by a simple approach. As an efficient sulfur host material, in an ultralow‐concentration KOH solution (0.1 m ), Se1.0 ‐Co3 S4 ‐VS/Se ‐VCo presents outstanding durability up to 165 h and a low overpotential of 289.5 mV at 10 mA cm –2, which outperform the commercial Co3 S4 nanosheets (NSs) and RuO2 . Moreover, the turnover frequency of Se1.0 ‐Co3 S4 ‐VS/Se ‐VCo is 0.00965 s –1 at an overpotential of 0.39 V, which is 5.7 times that of Co3 S4 NSs, and 5.8 times that of commercial RuO2 . The finding offers a rational design strategy to create the multi‐defect structure in catalysts toward high‐efficiency water electrolysis. Abstract : Well‐coupled Se doping and Co3 S4 nanosheets (NSs) stabilize atomically dispersed Co and S (Se) by taking advantage of abundant dangling unsaturated S and Co vacancies with superior performance for the oxygen evolution reaction, revealing that the appropriate combination of atom defect structures is expected to optimize the adsorption energy for the catalytic process.